Determination of proper band size for stainless steel crowns of primary second molars: A cross-sectional study - Mohammad Moradinia; Hamid Sarlak; Elham Mohammad-Rabei; Amir Almasi-Hashiani; Alireza Shamsi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND AND OBJECTIVES: Fixed space maintainers are often used following primary tooth loss. In this process, selection of a proper band size for stainless steel crowns (SSCs) is often performed by trial and error, which increases the chairside time and risk of contamination of the tried bands with saliva, blood, and gingival crevicular fluid, necessitating their subsequent sterilization. This study is aimed at determining the proper size of prefabricated bands for all SSCs of primary second molars. MATERIALS AND METHODS: In this cross-sectional study, seven examiners, including three orthodontists and four pediatric dentists attempted to select the proper band size for 24 primary second molar SSCs (3M). They selected the proper band size for each size of SSC six times in three sessions. The significance of all selected choices was carried out using the test of proportions. RESULTS: The most commonly selected bands for EU2, EU3, EU4, EU5, EU6, and EU7 SSCs were sizes 31+, 32+, 34, 35+, 37, and 38, respectively, and the proper bands for EL2, EL3, EL4, EL5, EL6, and EL7 SSCs were sizes 30, 31+, 32+, 33+, 35 and 36+, respectively. The difference in the frequency ratio of different choices for all sizes of SSCs was significant (P < 0.05). CONCLUSION: The current study determined the proper band size for all SSCs of primary maxillary and mandibular second molars. This information can help dental clinicians in selecting the proper band size for SSCs without trial and error.